2016
DOI: 10.1002/mop.30225
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of inverse legendre microstrip filter

Abstract: The inverse Legendre filter response is derived and its property is analysed by providing the magnitude specifications in the passband and stopband. The inverse Legendre function requires the identical order n as its Legendre counterpart. A quantitative comparison is carried out between Chebyshev, inverse Chebyshev, Legendre and inverse Legendre to show the improved characteristics of the inverse Legendre filters depending on specifications and criteria. The inverse Legendre filter shows maximally flat charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Thin film microstrip filters have been studied before in different frequency bands [12][13][14][15][16][17], and successful results are obtained in these studies. In [12], the design and fabrication of a microstrip band-pass filter based on quadruplet geometry is reported, where the filter resembles elliptic function near passband and Chebyshev filter in the stopband.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thin film microstrip filters have been studied before in different frequency bands [12][13][14][15][16][17], and successful results are obtained in these studies. In [12], the design and fabrication of a microstrip band-pass filter based on quadruplet geometry is reported, where the filter resembles elliptic function near passband and Chebyshev filter in the stopband.…”
Section: Introductionmentioning
confidence: 99%
“…Thin film microstrip filters have been studied before in different frequency bands [12][13][14][15][16][17], and successful results are obtained in these studies. In [12], the design and fabrication of a microstrip band-pass filter based on quadruplet geometry is reported, where the filter resembles elliptic function near passband and Chebyshev filter in the stopband. Multi-band bandstop filters are designed by using embedded I-stubs within a microstrip structure in [15] at 2.5/6.78 GHz, whereas in [16] High Temperature Superconductor (HTS) is used for the fabrication of the bandstop filter for L-band applications and it is reported that HTS has better performance than their gold-based counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Mostly, work had been done on the FODs which can operate hardly up to a frequency of few hundred MHz. So, the benefits of fractional calculus discussed so far can be taken to GHz range by using various techniques for the design and implementation of microwave filters [27][28][29][30][31][32]. In [27], compact dual-band bandpass filters using microstrip lines were designed using the hybrid-coded GA. Sanada et al [28] used the GA method for designing transmission line filters with open-circuited stubs in shunt configuration and continuously varying transmission line matching circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Based on equal-length non-uniform coupled lines, a tripleband bandpass microwave filter was proposed by evaluating the system function of the filter in the Z-domain using discrete-time techniques and chain scattering matrices of transmission line elements [29]. Inverse Legendre filter response was derived in [30] and the filter implementation is shown in microstrip low pass configuration. Kim and Lee [31] demonstrated a method based on the Z-transform to cascade transmission line sections for the synthesis of unequal-length multi-section transmission lines for multiband applications.…”
Section: Introductionmentioning
confidence: 99%